PENGARUH KURS, INFLASI DAN INDEKS PRODUKSI INDUSTRI TERHADAP JAKARTA ISLAMIC INDEX PERIODE 2010-2019 - Indi Masita Lisdawami (Ulumuna: Jurnal Studi Keilsman, 2021)
This study aims to analyze the effect of macroeconomic factors on the Jakarta Islamic Index (JII). The variables in this study are exchange rate, inflation, and Industrial Production Index (IPI). This study uses the Autoregressive Distributed (ARDL) model. The data used in this study is secondary data in the form of monthly time series (time series) from January 2010 to December 2019 taken from publications from the Central Statistics Agency, Bank Indonesia, related journals and references. The results of this study are the exchange rate and inflation variables have a negative and significant effect on JII in the short and long term. Industrial Production Index (IPI) has no significant effect.